Intermittent screening and treatment with artemisinin-combination therapy versus intermittent preventive treatment with sulphadoxine-pyrimethamine for malaria in pregnancy: a systematic review and individual participant data meta-analysis of randomised clinical trials. (November 2021) - Gutman, Julie R; Khairallah, Carole; Stepniewska, Kasia; Tagbor, Harry; Madanitsa, Mwayiwawo; Cairns, Matthew; L'lanziva, Anne Joan; Kalilani, Linda; Otieno, Kephas; Mwapasa, Victor; Meshnick, Steve; Kariuki, Simon; et al.
Abstract: Background: In sub-Saharan Africa, the efficacy of intermittent preventive therapy in pregnancy with sulphadoxine-pyrimethamine (IPTp-SP) for malaria in pregnancy is threatened by parasite resistance. We conducted an individual-participant data (IPD) meta-analysis to assess the efficacy of intermittent screening with malaria rapid diagnostic tests (RDTs) and treatment of RDT-positive women with artemisinin-based combination therapy (ISTp-ACT) compared to IPTp-SP, and understand the importance of subpatent infections. Methods: We searched MEDLINE and the Malaria-in-Pregnancy Library on May 6, 2021 for trials comparing ISTp-ACT and IPTp-SP. Generalised linear regression was used to compare adverse pregnancy outcomes (composite of small-for-gestational-age, low birthweight (LBW), or preterm delivery) and peripheral or placental Plasmodium falciparum at delivery. The effects of subpatent (PCR-positive, RDT/microscopy-negative) infections were assessed in both arms pooled using multi-variable fixed-effect models adjusting for the number of patent infections. PROSPERO registration: CRD42016043789. Findings: Five trials conducted between 2007 and 2014 contributed (10, 821 pregnancies), two from high SP-resistance areas where dhfr/dhps quintuple mutant parasites are saturated, but sextuple mutants are still rare (Kenya and Malawi), and three from low-resistance areas (West-Africa). Four trials contributed IPD data (N=10, 362). At delivery, the prevalence of any malaria infection (relative risk [RR]=1.08, 95% CI 1.00-1.16, I 2 =67.0 %) and patent infection (RR=1.02, 0.61-1.16, I 2 =0.0%) were similar. Subpatent infections were more common in ISTp recipients (RR=1.31, 1.05-1.62, I 2 =0.0%). There was no difference in adverse pregnancy outcome (RR=1.00, 0.96-1.05; studies=4, N=9, 191, I 2 =54.5%). Subpatent infections were associated with LBW (adjusted RR=1.13, 1.07-1.19), lower mean birthweight (adjusted mean difference=32g, 15-49), and preterm delivery (aRR=1.35, 1.15-1.57). Interpretation: ISTp-ACT was not superior to IPTp-SP and may result in more subpatent infections than the existing IPTp-SP policy. Subpatent infections were associated with increased LBW and preterm delivery. More sensitive diagnostic tests are needed to detect and treat low-grade infections. Funding: Centers for Disease Control and Prevention and Worldwide Antimalarial Resistance Network.